2012
DOI: 10.1155/2012/290805
|View full text |Cite
|
Sign up to set email alerts
|

Stimulators and Activators of Soluble Guanylate Cyclase: Review and Potential Therapeutic Indications

Abstract: The heme-protein soluble guanylyl cyclase (sGC) is the intracellular receptor for nitric oxide (NO). sGC is a heterodimeric enzyme withαandβsubunits and contains a heme moiety essential for binding of NO and activation of the enzyme. Stimulation of sGC mediates physiologic responses including smooth muscle relaxation, inhibition of inflammation, and thrombosis. In pathophysiologic states, NO formation and bioavailability can be impaired by oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 138 publications
(174 reference statements)
1
55
0
3
Order By: Relevance
“…These results was confirmed by two different methods of NO quantification, including fluorescence (by using DAF-2DA) measuring the intracellular NO and by electrode measuring through conversion of nitrite (stable metabolite) to NO. Ataciguat is able to induce cGMP accumulation [21] which can activates NOS in endothelial cells, considering that the endothelium treatment with cGMP analogue also stimulated the NO production by NOS activation. Our results suggested that NO production is by a mechanism dependent of NOS activation, and independent of Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 99%
“…These results was confirmed by two different methods of NO quantification, including fluorescence (by using DAF-2DA) measuring the intracellular NO and by electrode measuring through conversion of nitrite (stable metabolite) to NO. Ataciguat is able to induce cGMP accumulation [21] which can activates NOS in endothelial cells, considering that the endothelium treatment with cGMP analogue also stimulated the NO production by NOS activation. Our results suggested that NO production is by a mechanism dependent of NOS activation, and independent of Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 99%
“…По оси абсцисс -варианты комбинированного воздействия препаратов; аддитивный вклад веществ в комбина-ции отражают столбцы (YC-1+SNP)* и (ТФ+YC-1+SNP)**. Данные представлены в виде М ± m из трех независимых экспериментов В заключение этого раздела следует отметить, что ТФ, пополняя ряды регуляторов рГЦ [74] (рис. 5), представ-ляет интерес для исследователей.…”
Section: исследования влияния тф на функциональную активность ргц троunclassified
“…In conditions associated with incremented oxidative stress, NO generation, diminished biological availability can lead to NO donor tolerance with prolonged use [24]. Two classes of compounds that activate sGC by NO-independent pathways are under investigation: sGC stimulators and sGC activators.…”
Section: Stimulators and Activators Of Soluble Guanylate Cyclasementioning
confidence: 99%
“…Riociguat significantly reduced systolic BP and systemic vascular resistance [25]. Activators of sGC can increase sGC enzyme activity even when it is oxidized and less responsive to NO [24]. BAY 58-2667 (Cinaciguat)…”
Section: Stimulators and Activators Of Soluble Guanylate Cyclasementioning
confidence: 99%
See 1 more Smart Citation